(untitled) (Research, Society and Development, 2021)
This study aims to determine the commercial expiration date of and characterize lactose-free artisanal ice cream with dairy and non-dairy bases. We evaluated four ice cream with different bases at 0, 7, 14, and 21 d of storage. Their centesimal composition was analyzed for proteins, lipids, ashes, carbohydrates, and moisture. The physicochemical properties analyzed included overrun, density, titratable acidity, pH, water activity, and total soluble solids. The L*, a*, b*, C*, and h* parameters were used to evaluate color. Microbiological analyses included Salmonella sp., coagulase-positive Staphylococci, coliforms at 45° C, and mesophilic and psychrotrophic heterotrophic bacteria. Sensory analysis analyzed the consumer profile and measured their acceptance and intent to purchase the samples, with the zero-lactose milk base obtaining the best nutritional values, the best sensory characteristics, and more than 70% intent to purchase, indicating that it is the most accepted formulation. All treatments had a shelf life of 21 d at −18° C.